Pengaruh P5 Terhadap Efektifitas Pembelajaran Pendidikan Keagamaan Katolik Di SMPK Celaket 21 - Angelina Febrianty Mukin; Yuni Setiani Merlianta Girsang; Skolastika Dinda Ayu Maharani; Intansakti Pius X (International Forum of Researchers and Lecturers, 2024)
Education is the most important sector in the rise of a nation and state. The pattern of education in Indonesia has undergone many changes from time to time, many changes have been raised or these changes, one of which is the emergence of an independent curriculum and creating a P5 learning program. This P5 learning runs effectively. With this P5 or Pancasila Student Profile is a good influence and reference in developing student competence and character which is the main goal of this independent curriculum. P5 has 5 dimensions, namely; The values of mutual aid, social justice, democracy, the One and Only God, and just and civilized humanity. This study aims to illustrate the importance of the role of P5 in Catholic Religious Education or other learning. The research methods that children use are observational research methods and use literature review research methods, and several other sources such as articles, journals, related books.